Aerodynamic Design Of A Roof Fairing For Trucks - Ismadi, Nurul Syamimi Zahirah (Universiti Sains Malaysia, 2022)
Carbon emission is the release of carbon into the atmosphere also known as greenhouse gas emissions is the main contributor to climate change in this world. In Malaysia, the transportation sector accounts for around 28% of total carbon emission, of which 85% comes from road transport (Mustapa & Bekhet, 2016). Therefore, it is important reduce the greenhouse gas (GHG) emissions to slow the climate change and also improve air quality. Drag reducing devices can help to decrease air resistance of a vehicles, thus the forces acting on the vehicles will be transfer more of that power produced by the engine into movement. Therefore, the purpose of this thesis is to study how the air flow behavior imposed on the truck with 20 m/s of velocity by simulation. Moreover, wind tunnel is used to observe the drag acting on the 3D model truck that are selected. Multiple velocities is used from 1 m/s to 15 m/s to observe the drag. The result shows that a cab roof fairing that has rounded edges at the end could help to decrease the aerodynamic drag. In the simulation, the gap between the truck and trailer has created a low-pressure area which also contribute to the aerodynamic drag. Therefore, the use of cab roof fairing in the experiment, aerodynamic drag is reduced for about 5.86% at the velocity of 15 m/s.